New taxonomic data on the genus Zodariellum (Araneae, Zodariidae), with description of a new species from Kazakhstan - Shafaie, Sepideh; Pekár, Stano (Zootaxa, 2025)
A new zodariid species, Zodariellum martinae sp. nov. (♂♀), is described from southeastern Kazakhstan. Furthermore, type specimens of Z. mongolicum Marusik & Koponen, 2001 (♂) and Z. schmidti Marusik & Koponen, 2001 (♂♀), along with comparative material of Z. nenilini (Eskov, 1995) (♂♀), have been re-examined and photographed.
Keywords: velikost těla; Kazachstán; Male; Organ Size; Kazakhstan; Animal Structures; Ecosystem; Animals; ekosystém; Animal Distribution; zvířata; rozšíření zvířat; mužské pohlaví; Body Size; Spiders; ženské pohlaví; pavouci; Female; anatomické struktury zvířat; velikost orgánu